Gender stereotypes and values of modern Ukrainian society - Vera Sinyakova (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The article is a study of gender stereotypes and values of modern Ukrainian society. In the article the essence of gender representations of modern teenagers, found the idea of modern teenagers about gender roles and patterns of behavior of boys and girls. The article specifies the representation of boys and girls of the essential characteristics of gender roles. Also studied was the content of gender stereotypes, attitudes and values about adolescent characteristics, place and role of women and men in society.